A Rare Case of Fetal Mummification in Labrador Bitch - Sharma, Ankita (International Journal of Livestock Research, 2023)
Fetal mummification is defined as the resorption of fetal fluid within the uterus as the cervix remains closed due to the presence of the corpus luteum on the ovary. In canines’ papyreous type of mummification occurs. Fetal mummification in canines is unusual. The present case was reported in a Labrador female dog where two foetuses were removed out of which one was mummified and the other was normally grown but dead. Both the foetuses were removed by caesarean section. The bitch was recovered following post-operative management.